2008
DOI: 10.1080/02652030802112619
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of pregnant sows with mycotoxin-contaminated diets and their non-effect on foetal and maternal hepatic transcription of genes of the insulin-like growth factor system

Abstract: The insulin-like growth factor (IGF) system regulates foetal and placental growth. It can be influenced by dietary factors, but little is known about the effects of mycotoxin feeding on hepatic levels of the IGF system. The aim was (1) to determine the normal foetal and maternal hepatic transcription of major IGF genes at distinct stages of pregnancy and (2) to find out if the mycotoxins deoxynivalenol (DON) and zearalenone (ZON) affect transcript concentrations. Pregnant sows were fed with naturally contamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A single species of fungi might produce one or several mycotoxins, and individual mycotoxins might be produced by different fungal species [48]. Many studies have shown that the animal feed could be contaminated by several mycotoxins [41,49,50]. The deleterious effects of a single mycotoxin have been detected less frequently, particularly in gestational sows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single species of fungi might produce one or several mycotoxins, and individual mycotoxins might be produced by different fungal species [48]. Many studies have shown that the animal feed could be contaminated by several mycotoxins [41,49,50]. The deleterious effects of a single mycotoxin have been detected less frequently, particularly in gestational sows.…”
Section: Discussionmentioning
confidence: 99%
“…Zearalenone was the major contaminant and was 2.77 mg/kg in the contaminated diets and 2.76 mg/kg in the MHNT group. Analysis of the corn and diet by Gas Chromatography-Mass Spectrometer for a detailed characterization of the trichothecene mycotoxin pattern revealed that B-trichothecene mycotoxins, such as 15-acetyldeoxynivalenol, 3-acetyldeoxynivalenol, and nivalenol, and A-trichothecene mycotoxin HT-2 toxins were lower than the detection limits [41]. Water was provided ad libitum.…”
Section: Animals Exposure To Zen and The Experimental Designmentioning
confidence: 99%
“…Feeding of the contaminated diet exerted no effects on these genes. This suggests that deoxynivalenol and zearalenone-contaminated diets can induce growth depression in sows and piglets during pregnancy without affecting hepatic transcription of major IGF genes (Tiemann et al, 2008a).…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…This suggests that deoxynivalenol and zearalenone-contaminated diets can induce growth depression in sows and piglets during pregnancy without affecting hepatic transcription of major IGF genes (Tiemann et al, 2008a). This suggests that deoxynivalenol and zearalenone-contaminated diets can induce growth depression in sows and piglets during pregnancy without affecting hepatic transcription of major IGF genes (Tiemann et al, 2008a).…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…trichothecene mycotoxins, such as HT-2 toxin, were lower than the detection limits (Tiemann et al 2008). Water was provided ad libitum.…”
Section: Animals and Experimental Designmentioning
confidence: 99%